Estudio físico-químico comparativo de lixiviación con cianuro y tiourea en concentrados de oro, procedente de la planta de beneficio “Franromec” del cantón Camilo Ponce Enríquez, Provincia del Azuay. - Guerrero Rodríguez., Ricardo Ignacio (2015)
This research project deals with the study of leaching of gold ore concentrates by flotation, like using cyanide and thiourea leaching agents. Cyanide has been used for over 100 years in the recovery of gold and silver because it is an economic and cost-effective process, however the cyanide has been restricted by its toxic nature which makes it harmful to humado and nature.